Delineating Molecular Mechanisms of Squamous Tissue Homeostasis and Neoplasia: Focus on p63 - Kathryn E. King; Linan Ha; Tura Camilli; Wendy C. Weinberg (Journal of Skin Cancer)
Mouse models have informed us that p63 is critical for normal epidermal development and homeostasis. The p53/p63/p73 family is expressed as multiple protein isoforms due to a combination of alternative promoter usage and C-terminal alternative splicing. These isoforms can mimic or interfere with one another, and their balance ultimately determines biological outcome in a context-dependent manner. While not frequently mutated, p63, and in particular the ΔNp63 subclass, is commonly overexpressed in human squamous cell cancers. In vitro keratinocytes and murine transgenic and transplantation models have been invaluable in elucidating the contribution of altered p63 levels to cancer development, and studies have identified the roles for ΔNp63 isoforms in keratinocyte survival and malignant progression, likely due in part to their transcriptional regulatory function. These findings can be extended to human cancers; for example, the novel recognition of NFκB/c-Rel as a downstream effector of p63 has identified a role for NFκB/c-Rel in human squamous cell cancers. These models will be critical in enhancing the understanding of the specific molecular mechanisms of cancer development and progression.